RAS (REFLECTIVE ANALOGY AND SUMMARY): A STRATEGY TO ENHANCE GRADE 7 STUDENTS’ LITERARY SKILLS - Vecaldo, Vanessa Joy (International Journal of Arts, Sciences and Education, 2024)
Part of the string of abilities or skills that need to be developed and enhanced among learners is their understanding and appreciation of literature. Along this line, the researcher explored the effects of the strategy, R.A.S. (Reflective Analogy and Summary), in enhancing Grade 7 students’ literary skills. The study employed the quasi-experimental research design with experimental and control groups of 30 participants each from Tuguegarao City Science High School, Cagayan National High School, and Linao National High School - schools in the Division of Tuguegarao City with Special Science Curriculum. After four (4) online sessions, the post-test was given to the students; since both groups are not normally distributed, the researcher employed non-parametric tests. Results showed that the post-test scores of the students in the experimental group were significantly higher than those of the control group students. Moreover, the post-test scores are significantly higher than the pretest results. With these, it can be concluded that using RAS enhances Grade 7 students’ literary skills more effectively.